The Impact Of Employee Performance On Employee Productivity: Based On The Work Environment, Standard Operating Procedures (SOP), And Work Discipline - Windarko, Windarko; Lastro, Djano; Iskandar, Yusuf; Mala, Chajar Matari Fath (IJBLE Scientific Publications Community Inc., 2023)
This research explores the complex relationship between employee performance and productivity within a company. Typically, research related to performance and productivity focuses on the skills of employees as well as their motivation or incentives. In this case, the researcher aims to examine performance and productivity from three other crucial factors: the work environment, Standard Operating Procedures (SOP), and work discipline. This is because it has been found that these three factors can also influence an employee's performance, ultimately impacting their productivity while working. The research results will reveal whether a positive work environment can have a positive impact on performance. Similarly, the increasing strictness of SOPs and the discipline in following them can also have a positive effect on both performance and productivity.